Miniaturized Single-Feed Multiband Patch Antennas - Boukarkar, Abdelheq; Xian Qi Lin; Yuan Jiang; Yi Qiang Yu (IEEE transactions on antennas and propagation, 2017)
This communication introduces an approach for designing miniaturized single-feed multiband patch antennas. The size reduction is obtained by loading shorting metalized vias on one edge of the radiating patch, while multiband is obtained by etching inverted multiple U-shapes. A dual-band antenna with a large measured frequency ratio of 2.74 is first discussed. Then triple-band, and further quad-band antennas are, respectively, designed. The antennas have sufficient electrical small size when considering the radius of the minimum enclosing sphere to the radiating patch. A radius value of 0.09λ 0 is obtained for the quad-band antenna with respect to the lowest operating frequency centered at 3.04 GHz. Simulated and measured results of the antennas' reflection coefficient and radiation patterns are provided. Good agreement between the simulation results and measurement results is achieved. The antennas' measured peak gains and efficiencies vary from 1.43 to 3.06 dBi and 42% to 74%, respectively. Compared with other designs, the proposed antennas exhibit multiband performance by using a simple single-feed structure, realize different combinations of highly isolated frequency bands with wide tunability of frequency ratios, and have directional stable radiation patterns that are compact and of electrically small size. Indeed, they have the potential to meet the practical requirements for wireless applications.